PROBLEMS OF FINANCING AND ENSURING THE FINANCIAL SUSTAINABILITY OF HIGHER EDUCATION INSTITUTIONS IN UKRAINE DURING THE WAR PERIOD - Zatonatskiy, Dmytro; Farion, Demian (Socio-economic relations in the digital society, 2023)
Funding the education system throughout life and ensuring the financial stability of higher education institutions of Ukraine during the war period are considered today by the world community as an investment in human and social capital, which today should ensure the preservation of the country’s scientific and educational potential, and with proper governance - socio-economic growth and increasing the competitiveness of the state in the future. The article examines the problem of the imperfection of the models for organizing financial support and managing the financial stability of higher education institutions in Ukraine during the wartime period. Particular attention is focused on the analysis of planned and actual expenditures on education and science, the reasons for their significant reduction, and the consequences of such a sharp reduction in funding. In the course of writing the article, approaches to determining the directions of off-budget financing of higher education institutions in Ukraine during the war period are proposed. The authors deepened the diagnosis of the level of involvement of various stakeholders in the financing of educational needs during the war period. With the help of the application of a wide range of general scientific and specific methods, conclusions aimed at increasing the financial stability of higher education institutions of Ukraine during the war period were formed.